1992
DOI: 10.2337/diab.41.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Increases Insulin Sensitivity by Activating Insulin Receptor Kinase

Abstract: A new oral agent, 5-[4-(2-(5-ethyl 12-pyridyl)ethoxy]- benzoyl]-2,4-thiazolidinedione (pioglitazone), has been developed for treatment of non-insulin-dependent diabetes mellitus (NIDDM). This agent increases insulin sensitivity in vivo in genetically obese Wistar fatty rats. Administration of the agent (3 mg/kg/day) for 10 days to the rats ameliorated hyperglycemia and hyperinsulinemia, indicating that it decreased insulin resistance. To clarify the mechanism of the drug to increase insulin sensitivity, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…Multiple studies have shown that thiazolidinediones improve hepatic insulin action relative to placebo (6,16,30,31). The present studies establish that thiazolidinediones also improve hepatic insulin action relative to metformin.…”
Section: Discussionsupporting
confidence: 62%
“…Multiple studies have shown that thiazolidinediones improve hepatic insulin action relative to placebo (6,16,30,31). The present studies establish that thiazolidinediones also improve hepatic insulin action relative to metformin.…”
Section: Discussionsupporting
confidence: 62%
“…11,14 Although the mechanisms by which thiazolidinedione derivatives improve insulin resistance are not entirely understood, a wide variety of mechanisms has so far been proposed. Pioglitazone was reported to ameliorate insulin resistance by increasing insulinstimulated autophosphorylation of insulin receptor and its kinase activity, 15 whereas this agent caused no increases in autophosphorylation and kinase activity of the receptor in the corresponding lean littermates. Under the same conditions, plasma insulin and triglyceride (TG) concentrations were signi®cantly decreased by this agent although plasma glucose concentration remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…The α subunit is responsible for binding insulin, whilst the β subunit has intrinsic tyrosine protein kinase (TPK) activity that initiates downstream intracellular signaling events (27). Numerous studies have demonstrated that diabetic hyperglycemia is associated with aberrant insulin receptor phosphorylation and reduced TPK activity (28,29). In the present GK model, insulin Rβ dual tyrosine 1162 and 1163 phosphorylation was markedly reduced.…”
Section: Discussionmentioning
confidence: 71%